Difficulties Faced by Married Female Employees at the University of Zakho - Abdullah, Sajida Ismail (Journal of Humanities & Social Sciences, 2024)
The research aimed to investigate the challenges faced by married female employees at the University of Zakho, assess whether there are significant differences in their experiences based on the years of marriage and identify the underlying areas of difficulty. The research community, employees in all departments in the faculties of the University of Zakho. The research community number was (309) in focusing on married employees which were (187). This work depended on (intentional randomness) method for selecting the research community of women employees at the University of Zakho in various faculties. The research tool was a ready-made scale Sibaay (2004) for employed women. Furthermore, the scale consisted in the final form on (32) items distributed on three alternatives (always - sometimes - never). Whereas the researchers used statistical methods such as:  the “T” test for one sample of the members of the research sample and the T test for two independent samples of the research sample members, the weighted mean, and the standard deviation for each paragraph. The results revealed that there are difficulties prevalent among working women, particularly in childcare, spousal care, household chores, social burdens, and administrative responsibilities. The study concludes with recommendations aimed at addressing the identified challenges and strengthening support systems for married female employees at the University of Zakho.
Keywords: Difficulties of Female Employees; Homework; Job performance; Zakho University